POTRET KETERWAKILAN PEREMPUAN DALAM WAJAH POLITIK INDONESIA PERSEPEKTIF REGULASI DAN IMPLEMENTASI - Ningsih, Julia Sintia; Jidin, Habila; Maharani, Rizki (Bahasa Indonesia, 2024)
This study discusses the description of women's representation in the realm of political politics by paying attention to the perspective of regulation and implementation. The study focused on women's political rights, all of which stated that women have the same political rights as men. By using qualitative research methods. This study concludes that women's representation in the political system has a very important role to create a gender-just political system because if women's representation is replaced by men, the mechanism in gender justice will turn into a gender bias where women are still applied unfairly and this can also be said to be a partial and detrimental condition. the representation of women in politics is a manifestation of the fulfillment of citizenship rights, namely the right granted by the state to a citizen or community to have the right to participate in the political field whose mechanism has been regulated in legislation.